Características epidemiológicas dos casos notificados de dengue no município de Vitória-ES no período 2018-2020 - Resende, Lilyan Correia (2023)
Introduction: Dengue is an acute systemic viral infection transmitted by Aedes aegypti mosquitoes. Due to the distribution of this mosquito throughout the national territory and the constant change in circulating serotypes, Brazil is the country with the highest number of cases in the Americas. More than 11 million cases of dengue have already been reported since 1985, with the establishment of endemic cycles throughout the national territory and peaks of cases in an approximate interval of three years. Thus, dengue is characterized as the most important arbovirus in Brazil, causing epidemics which greatly impact the public health and brings mortality. Objective: To elucidate the determining factors involved in the spread of dengue, contributing to discussions on the subject and proposing integrative measures between the Epidemiological Surveillance and the community, and contributing to control dengue in the municipality of Vitória. Methods: The study was based on the city of Vitória, Espirito Santo. Dengue cases with diagnosis confirmed in the years of 2018 to 2020 were extracted from the disease notification database. The monthly incidence in Vitória as a whole and in each neighborhood that makes up the municipality was calculated. The spatial distribution was verified annually which generated relative risk maps by neighborhood and clusters maps. Regarding the statistical analysis, the chi-square method was used to verify the association between the variables sex, race, education and age, and the presence of the disease. Results: Two epidemic peaks were observed, in May 2019 and January 2020, separated by a period of low rainfall. The incidence in the years 2018, 2019 and 2020 were 359.2, 2018.3 and 2480.5 cases per 100,000 inhabitants, respectively. From the spatial point of view, a centrifugal dispersion was observed, which began in the region of Santo Antônio, covering contiguous areas such as Centro, São Pedro and Maruípe. There was a greater association of dengue with women , afrodescendants, and individuals less educated. Regarding the age distribution, individuals most at risk were adolescents, followed by adults, elders and children, which shows a relative predominance of young risk groups for de occurrence of dengue. Conclusion: An epidemic was observed after four years, an interepidemic time that is common in endemic cycles observed in Brazil. Among the factors associated with the increase in cases frequency along the period, the reemergence of DENV-2, a serotype that had not circulated since 2011, and the high rainfall in 2019 stand out. The regions of São Pedro and Santo Antônio need integrative measures, which involve health authorities and civil society, as they are areas with less autonomy in regulating and controlling mosquito breeding sites. The increased incidence in younger age groups also shows a change in the epidemiological pattern of dengue in Vitória.